MODEL PEMBERDAYAAN MASYARAKAT TANI BERBASIS KEMITRAAN GENDER DAN KOMODITI UNGGULAN LOKAL DALAM RANGKA PENGENTASAN KEMISKINAN DI PEDESAAN - kardaya, dede (Universitas Djuanda Bogor, 2010)
Agricultural sector in a wide perspective (food crop, animal husbandry, mixed farming) is very potential in helping Indonesian people cope with the effects of global and national economic crisis. The optimization of agricultural potential can lead people in rural areas to food sovereignty and at least reduce hunger. The concept of gender and family empowerment is seen as an entry point to poverty eradication a family is the smallest institution in a society and partnership cooperation between male and female in a family is a foundation for the achievement of family prosperity. Public prosperity is achieved when family prosperity is. Therefore, this study was done in order to assess the characteristics of farmer families seen from various aspects. Results showed that most proportion of husband-wife groups were middle-aged and had highest educational level of elementary school. More than half of husband respondents (61.3% in Tasikmalaya Regency and 60.0% in Ciamis Regency) worked as farmers. More than half of wife respondents (61.3% in Tasikmalaya Regency and 60.0% in Ciamis Regency) were housewives. The highest percentage of respondents (64.0%) had 1-4 family members with total income of less than Rp500,000 per month and an average income of Rp766,421. The highest proportion of respondents spent Rp 183,289 (in Tasikmalaya Regency) and Rp157,857 (in Ciamis Regency) per month for household appliance repair. The highest percentage of respondents (29.3%) stated that individual as source of loan. The most common problem faced by respondents in Tasikmalaya and Ciamis Regencies was financial problem and the least common was food availability. Respondents in Tasikmalaya Regency faced family problems more often than those in Ciamis Regency. The strategy most commonly applied by families in both regencies to save expenses was buying cheaper food. There was a positive relationship between wife age (r = 0.204; p = 0.012), husband age (r = 0.240; p = 0.003), and wife education (r = 0.212; p = 0.009) and family problems. A positive relation was also found between husband education and coping strategy applied (r = 0.163; p =0.046). Number of family member had a positive correlation with amount of debt (r = 0.243; p = 0.003) indicating the more members a family had, the more debt the respondent had.